Strategi Pelayanan Kepada Konsumen Di Agen Pos Gunung Sari Indah-Surabaya - Kornelia Sarce; Achmad Daengs GS (Universitas 45 Surabaya, 2023)
AgenPos is a network development concept through partnership cooperation between PT Pos Indonesia and individuals or business entities in order to provide wider postal services to the community. The practice of conducting Field Work Lecture activities lasts for one month, starting from May 1, 2023 to June 1, 2023. The package delivery input system and payment input system, along with the realization review that has been carried out by the Gunung Sari Indah Post agent is very good and contributes greatly to the target at the Gunung Sari Indah Postal Agent, but there are obstacles that occur as well as balance changes in the postal agent program, both for payments and for shipments so that the company has to lose customers. The advice that the author can give is to retain customers, improve optimal service so as to create customer satisfaction and establish good relationships with customers as a form of customer retention strategy.